The Contrarian Investment Strategy does not Work in Canadian Markets - Kryzanowski, Lawrence; Zhang, Hao (Journal of Financial and Quantitative Analysis, 1992)
This paper tests the overreaction hypothesis using monthly data for stocks listed on the Toronto Stock Exchange over the 1950–1988 period. Unlike De Bondt and Thaler (1985), (1987), it finds statistically significant continuation behavior for the next one (and two) year(s) for winners and losers, and insignificant reversal behavior for winners and losers over longer formation/test periods of up to ten years. While the systematic risks of the winners decrease significantly over all test periods, the systematic risks of the losers increase significantly for only the 12-month formation/test periods (unlike Chan (1988)). The only significant change in variance from the formation to test periods occurs for the losers for the 12-month formation/test periods. The findings are robust for January versus non-January and size-based portfolios (unlike Zarowin (1989), (1990)). The findings are robust for various performance measures (specifically, market-adjusted CAR, and the Jensen (1968) and Sharpe (1966) portfolio performance measures).